Response of Sugarcane in a Red Ultisol to Phosphorus Rates, Phosphorus Sources, and Filter Cake - Gustavo Caione; Renato de Mello Prado; Cid Naudi Silva Campos; Leandro Rosatto Moda; Ricardo de Lima Vasconcelos; João Martins Pizauro Júnior (The Scientific World Journal)
We evaluated the effect of phosphorus application rates from various sources and in the presence or absence of filter cake on soil phosphorus, plant phosphorus, changes in acid phosphatase activity, and sugarcane productivity grown in Eutrophic Red Ultisol. Three P sources were used (triple superphosphate, Araxa rock phosphate, and Bayovar rock phosphate) and four application rates (0, 90, 180, and 360 kg ha−1 of P2O5) in the presence or absence of filter cake (7.5 t ha−1, dry basis). The soil P, the accumulated plant P, the leaf acid phosphatase activity and straw, the stalk productivity, the concentration of soluble solids in the juice (Brix), the juice sucrose content (Pol), and the purity were the parameters evaluated. We found that P applications increased levels of soil, leaf, and juice phosphorus and led to higher phosphorus accumulation and greater stalk and straw productivity. These levels were highest in the presence of filter cake. Acid phosphatase activity decreased with increasing plant phosphorus concentration. Phosphate fertilization did not show effect on sugarcane technological quality. We concluded that P application, regardless of source, improved phosphorus nutrition and increased productivity in sugarcane and, when associated with filter cake, reduced the need for mineral fertilizer.